Louis Braille, the boy who invented books for the blind. - Davidson, Margaret, 1936-; Compere, Janet (New York, Hastings House, 1972)
The life of the 19th-century Frenchman who invented an alphabet enabling the blind to read
Keywords: Braille, Louis, 1809-1852 -- Juvenile literature; Braille, Louis, 1809-1852; Blind; Physically handicapped